Management Of Frozen Shoulder In Diabetes Mellitus Through Valuka Sveda (Ushma Method) –A Case Series - M, Nusriya; VR, Subin (International Research Journal of Ayurveda & Yoga, 2021)
Frozen shoulder is a clinical syndrome characterized by painful restriction of both active and passive movements of shoulder. It is having an incidence of 2% in general population and 10-30% in diabetes mellitus. Svedana is one of the most common procedure done in Panchakarma, is practiced as an important preparatory measure before Sodhana therapy. In addition, it is an independent therapeutic measure for the management of many diseases. Valuka is an important, easy and effective material for Rooksha Sveda, and is mentioned in both Tapa and Ushma Sveda in classics. The aim of the current study was to clinically evaluate the Ushma method of Valuka Sveda in the management of Frozen shoulder of diabetes mellitus. This case series includes 13 diagnosed patients of Frozen Shoulder of Diabetes mellitus and was received Ushma method of Valuka Sveda for 14 days. The assessments were done on Shoulder Pain and Disability Index (SPADI), and Goniometry before trial, after trial and after follow up. After the course of treatment significant results were found in reducing SPADI score and in improving range of movements.